Implementating ‘Calistung’ Clinic Program to Overcome Students’ Reading Difficulty - Silvio Juliana Nabela; Ali Mustadi; Maulina Hendrik; Romadon Romadon (STAI Hubbulwathan Duri, 2022)
There were 8 chlidren who had difficulty reading in grade I Ibnu Khaldun, every child has different reading difficulty. This study aims to identify reading difficulties experienced by students and the application of the reading, writing, and counting skills (Calistung) clinic program in overcoming students' reading difficulties. This study used a qualitative descriptive method. Data were collected through observation, interviews, and documentation followed by data triangulation. Data analysis was performed through data reduction, data display and conclusion drawing/verification. Based on the results of the study, the reading difficulties experienced by students were recognizing letters such as pronouncing the letter incorrectly; distinguishing similar letters adversely; stuttering, connecting syllables, reading simple words and sentences; and difficulty in reading consonants, vowels, and diphthongs. Students who have reading difficulties were assisted through the Calistung clinic program.